Treatment-induced neuropathy of diabetes: an update - Quiroz-Aldave, Juan Eduardo (2023)
Background and aims: Treatment-induced neuropathy of diabetes is an acute small-fibre neuropathy associated with rapid glycaemia improvement. Methods: This study is a narrative review carried out based on a bibliographic review, using articles indexed in PubMed/Medline and Scielo. Results: This entity is more frequent in adult patients with poor previous glycaemic control. Its precise pathophysiology is unknown, but it is likely related to unrestored microcirculation changes that occurred during the hyperglycaemic period. It presents with intense, sudden neuropathic pain and autonomic dysfunction after a rapid glycaemic correction and a poorer analgesic response than in diabetic neuropathy. Conclusions: Since rapid glycaemia correction is the cause of this problem, clinical practice guidelines that can help physicians to prevent, diagnose and manage this entity should be developed. Copyright © 2023 John Wiley & Sons.